SARS-CoV-2-mediated liver injury: pathophysiology and mechanisms of disease - Choaib, Ali (2022)
Background SARS-CoV-2-induced severe inflammatory response can be associated with severe medical consequences leading to multi-organ failure, including the liver. The main mechanism behind this assault is the aggressive cytokine storm that induces cytotoxicity in various organs. Of interest, hepatic stellate cells (HSC) respond acutely to liver injury through several molecular mechanisms, hence furthering the perpetuation of the cytokine storm and its resultant tissue damage. In addition, hepatocytes undergo apoptosis or necrosis resulting in the release of pro-inflammatory and pro-fibrogenic mediators that lead to chronic liver inflammation. Aims The aim of this review is to summarize available data on SARS-CoV-2-induced liver inflammation in addition to evaluate the potential effect of anti-inflammatory drugs in attenuating SARS-CoV-2-induced liver inflammation. Methods Thorough PubMed search was done to gather and summarize published data on SARS-CoV-2-induced liver inflammation. Additionally, various anti-inflammatory potential treatments were also documented. Results Published data documented SARS-CoV-2 infection of liver tissues and is prominent in most liver cells. Also, histological analysis showed various features of tissues damage, e.g., hepatocellular necrosis, mitosis, cellular infiltration, and fatty degeneration in addition to microvesicular steatosis and inflammation. Finally, the efficacy of the different drugs used to treat SARS-CoV-2-induced liver injury, in particular the anti-inflammatory remedies, are likely to have some beneficial effect to treat liver injury in COVID-19. Conclusion SARS-CoV-2-induced liver inflammation is a serious condition, and drugs with potent anti-inflammatory effect can play a major role in preventing irreversible liver damage in COVID-19.